Feed intake, nutrient utilization and growth performance of West African Dwarf rams fed silage combinations of maize forage and mucuna pruriens foliage (2017)
Crude protein is essentially needed for ruminants but expensive to supply. Mucuna puriens is a high yielding domesticated legume. When the legume is strategically combined with a fibre source, it will make a good diet for ruminants. Thus, a study was carried out to assess the effect of ensiling mucuna with maize forage on performance of rams. In the study, rams were fed silage combinations of Maize Forage (MF) and Mucuna pruriens foliage (MPF). Downy mildew and streak resistant (DMR-SR) yellow variety maize was planted and harvested as MF at six weeks of growth and ensiled with MPF at four levels: 1:0, 3:1, 1:1 and 1:3 for 21 days. All the four silages were fed to 20 WAD rams (12.00±0.25 Kg) in a completely randomised design for 105 days. Proximate composition of the silages, apparent nutrient digestibility of silages in WAD rams, feed intake and weight changes were determined using standard procedures, while feed conversion ratio was computed using standard procedures. Data obtained were analysed using descriptive statistics and ANOVA at α(0.05) The dry matter (DM) was significantly higher in T1 (25.65±0.62) and T2 (23.48±0.47) than T3 (21,80±0.41) and T4 (21.57±0.40). The crude protein (CP) was highest in T4 (13.0±0.6) and least in T1 (8.0±0.2). The crude fibre was significantly higher in T1 (26.4±2.6) and T2 (26.2±2.0) than T3 (24.0±1.8) and T4 (21.6±0.9). Apparent digestibility of neutral detergent fibre (NDF) was highest in T2 (59.2±1.7) and least in T4 (37.7±1.9), while percentage nitrogen retention was significantly higher in T2 (43.2x±3.8) and lower in T1 (20.0x4.3). The FCR for rams fed T2 was significantly lower (8.84±1.2) than T1 (9.76±0.80), T3 (9.60±0.60) and T4 (11.50±0.90) Ensiling maize forage with Mucuna pruriens foliage at 3:1 enhanced nutrient digestibility and growth performance in West African dwarf rams without any deleterious effect.